The Impact of Non-normative Displays of Emotion in the Workplace: How Inappropriateness Shapes the Interpersonal Outcomes of Emotional Displays - Cheshin, Arik (Frontiers in Psychology, 2020)
When it comes to evaluating emotions as either “good” or “bad” everyday beliefs regarding emotions rely mostly on their hedonic features – does the emotion feel good to the person experiencing the emotion. However, emotions are not only felt inwardly; they are also displayed outwardly, and others’ responses to an emotional display can produce asymmetric outcomes (i.e., even emotions that feel good to the displayer can lead to negative outcomes for the displayer and others). Focusing on organizational settings, this manuscript reviews the literature on the outcomes of emotional expressions, and argues that the evidence points to perceived (in)appropriateness of emotional displays as key to their consequences: emotional displays which are deemed inappropriate generate disadvantageous outcomes for the displayer, and at times also the organization. Drawing on relevant theoretical models (Emotions as Social Information [EASI] theory, the Dual Threshold Model of Anger, and Asymmetrical Outcomes of Emotions), the paper highlights three broad and interrelated reasons why emotion displays could be deemed unfitting and inappropriate: (1) characteristics of the displayer (e.g., status, gender); (2) characteristics of the display (e.g., intensity, mode); and (3) characteristics of the context (e.g., national or organizational culture, topic of interaction). The review focuses on three different emotions – anger, sadness, and happiness – which differ in their valence based on how they feel to the displayer, but can yield different interpersonal outcomes. In conclusion, the paper argues that inappropriateness must be judged separately from whether an emotional display is civil (i.e., polite and courteous) or uncivil (i.e., rude, discourteous, and offensive). Testable propositions are presented, as well as suggested future research directions.